CO2 methanation over Ni/ZSM-5 catalysts: The effects of support morphology and La2O3 modification. (15th September 2022) - Cui, Yan; Qiu, Jian; Chen, Bin; Xu, Leilei; Chen, Mindong; Wu, Cai-e; Cheng, Ge; Yang, Bo; Wang, Ning; Hu, Xun
Graphical abstract: Highlights: The ZSM-5 with short b-axis was synthesized by the hydrothermal method. The Ni-based catalysts supported on ZSM-5 with different morphologies. The influence of morphology on Ni-based CO2 methanation catalyst was studied. The La doped catalyst with short b-axis ZSM-5 support showed the optimum performance. The reaction intermediates of CO2 methanation studied by in-situ DRIFTS. Abstract: A series of Ni-based catalysts supported on the ZSM-5 with different morphologies were facilely synthesized and employed as the CO2 methanation catalysts. The achieved catalysts were systematically characterized by various techniques. Besides, the in-situ DRIFTS was also performed to investigate the intermediates of the CO2 methanation reaction process. It was found that the catalyst with the short b-axis ZSM-5 support displayed much higher activity than other counterparts supported on nano ZSM-5 and commercial ZSM-5. The possible reason for this could be attributed to the unique morphology of short b-axis ZSM-5 zeolite with large external surface area (489.7 m 2 /g). In addition, it was also found the La doped catalyst displayed much higher low-temperature activity (200–300 °C) and CH4 selectivity than the pristine counterpart without modification. Resultantly, the catalyst with both the short b-axis ZSM-5 support and La2 O3 modification displayed the optimum catalytic performance. Therefore, the morphology of the support and the selection of modifier were considered as the important concerns when designing and synthesizing Ni based CO2 methanation catalysts with highly-developed performances.